Knowledge and attitude regarding human papillomavirus vaccine and its associated factors among parents of daughters age between 9-14 years in central Ethiopia, 2021 - Haroma Humnesa; Mecha Aboma; Nagas Dida; Mitsiwat Abebe (AOSIS, 2022)
Background. Human Papillomavirus (HPV) is the most common sexually transmitted disease and the major cause of cervical cancer, which threatened the lives of several women and remains a critical concern in Africa and around the world. Ethiopia initiates the human papillomavirus vaccines on 3rd December 2018 for the primary time to vaccinate six million girls. Objective. This study assessed knowledge and attitudes toward the human papillomavirus vaccine among parents of daughters aged between 9 and 14 years in the Central Ethiopia. Methods. A community-based cross-sectional study was conducted on 619 parents whose daughters were aged between 9 and 14 years old from February 01 to February 30, 2021. A multistage sampling method was employed to select study participants. Data were collected using an interview administered questionnaire adapted from related literature. Descriptive, bivariate, and multivariate binary logistic regression analyses were done by using SPSS v. 20.0. Results.  A total of 619 parents participated in the current study of whom, only 242 (39.1%) and 249 (40.2%) of the respondents were knowledgeable and had a favorable attitude toward the HPV, respectively. Age (AOR 1.98, 95% CI: 1.07, 3.69), place of residence (AOR 3.6, 95% CI: 1.45, 8.92), and wealth status (AOR 1.89, 95% CI: 1.09, 3.26) was independently associated with the knowledge of parents toward the HPV. Conclusion.  Policymakers and other stockholders require more effort to provide a resource to enhance knowledge and attitudes toward the HPV through the mass media and other health education outlets.